GIScience I: Social histories and disciplinary crucibles. (February 2021) - Wilson, Matthew W.
In this first report, I overview research on storytelling of the histories of GIS. I suggest that these efforts reveal important pathways for thinking the current moment and conditioning technoscience futures. I argue that these stories around technology illustrate various disciplinary crucibles around technical practices and knowledge work. To report on progress in GIScience is also to narrate the moments of change in the discipline, whether marked as quantitative, qualitative, radical, critical, black, feminist, Marxist, indigenous, environmental, postcolonial, queer, or minor, among others. I suggest 'minor GISciences' to encourage attentiveness to the historical conditions and social implications of geographic technologies.